A band of bound states in the continuum induced by disorder - Yi-Xin Xiao (Nature Portfolio, 2018)
Abstract Bound states in the continuum usually refer to the phenomenon of a single or a few discrete bound states embedded in a continuous spectrum of extended states. Here we propose a simple mechanism to achieve a band of bound states in the continuum in a class of disordered quasi-1D and quasi-2D systems, where the bound states and extended states overlap completely in a spectral range. The systems are partially disordered in a way that a band of extended states always exists, not affected by the randomness, whereas the states in all other bands become localized and cover the entire spectrum of extended states. We demonstrate such disordered-induced bound states in the continuum in disordered multi-chain and multi-layer systems.